2009
DOI: 10.1007/s00125-009-1509-2
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular PBEF/NAMPT/visfatin activates pro-inflammatory signalling in human vascular smooth muscle cells through nicotinamide phosphoribosyltransferase activity

Abstract: Aims/hypothesis Extracellular pre-B cell colony-enhancing factor/nicotinamide phosphoribosyltransferase/visfatin (ePBEF/NAMPT/visfatin) is an adipocytokine, whose circulating levels are enhanced in metabolic disorders, such as diabetes mellitus and obesity. Here, we explored the ability of ePBEF/NAMPT/visfatin to promote vascular inflammation, as a condition closely related to atherothrombotic diseases. We specifically studied the ability of PBEF/ NAMPT/visfatin to directly activate pathways leading to inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 33 publications
3
102
1
1
Order By: Relevance
“…In endothelial cells, visfatin has ben shown to up-regulate the monocyte chemoattractant protein-1 and MMP-9 production (22)(23)(24). In smooth muscle cells, visfatin has been found to induce production of the pro-inflammatory factor, iNOS (10). This study demonstrates herein that visfatin induces EMMPRIN and MMP-9 in macrophages.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In endothelial cells, visfatin has ben shown to up-regulate the monocyte chemoattractant protein-1 and MMP-9 production (22)(23)(24). In smooth muscle cells, visfatin has been found to induce production of the pro-inflammatory factor, iNOS (10). This study demonstrates herein that visfatin induces EMMPRIN and MMP-9 in macrophages.…”
Section: Discussionsupporting
confidence: 50%
“…It has been demonstrated that visfatin up-regulates iNOS via the ERK1/2-NF-κB pathway in smooth muscle cells (10). Liu et al have reported that p38 and ERK1/2 phosphorylation is required in the monocyte chemotactic protein-1 and interleukin-6 inductions in endothelial cells (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably it may suggest that increased circulating level of Vistafin/NAMT is compensating response to mitigate EPC mobbing and differentiation through the NFkappaB pathway and to attenuate vascular reparation [26][27][28]. It is worth noting that vistafin/NAMT is able to mediate several biological actions on endothelial directly via EPC differentiation and indirectly involving in vascular reparation vascular smooth muscle cells, metalloproteinases and growth factors [29,30]. The Figure is presented principal schema explained the role of vistafin/NAMT in endothelial repair.…”
Section: Introductionmentioning
confidence: 99%